(untitled) (Ius Novum, 2023)
The text is an analysis of normative solutions regarding the participation of members of consular offices (Polish and foreign) in evidentiary activities undertaken in criminal proceedings. The issue of participation of Polish consular officials in the interrogation of defendants and witnesses was discussed (Article 177 § 1b point 2 of the Code of Criminal Procedure), as well as the interrogation of these participants in criminal proceedings by the consul as the body replacing the Polish court in this respect. These activities, in accordance with the will of the Polish legislator and the law of nations, are included in what is called criminal proceedings in international relations, but also in consular law. Considerations were also made regarding the right to refuse to testify, which members of consular posts are entitled to in the circumstances related to their function. In the author’s opinion, there may be consular secrecy in this respect, which is a form of functional or professional secrecy.